Aquimarina sp. Associated With a Cuticular Disease of Cultured Larval Palinurid and Scyllarid Lobsters - Ooi, Mei C.; Goulden, Evan F.; Trotter, Andrew J.; Smith, Gregory G.; Bridle, Andrew R. (Frontiers in Microbiology, 2020)
Shell (cuticular) disease manifests in various forms and affects many crustaceans including lobsters. Outbreaks of white leg disease (WLD) with distinct signs of pereiopod tissue whitening and death have been observed in cultured larvae (phyllosomas) of ornate spiny lobster Panulirus ornatus, eastern rock lobster Sagmariasus verreauxi and slipper lobster Thenus australiensis. This study aimed to characterise and identify the causative agent of WLD through morphological and molecular (16S rRNA gene and whole genome sequencing) analysis, experimental infection of damaged/undamaged P. ornatus and T. australiensis phyllosomas, and bacterial community analysis (16S rRNA gene ampliconnext generation sequencing) of P. ornatus phyllosomas presenting with WLD during an outbreak. Bacterial communities of WLD-affected pereiopods showed low bacterial diversity and dominant abundance of Aquimarina spp. compared to healthy pereiopods, which were more diverse and enriched with Sulfitobacter spp. 16S rRNA gene Sanger sequencing of cultures from disease outbreaks identified the dominant bacterial isolate (TRL1) asThe isolate was a Gram-negative, long non-flagellated rod with 100 % 16S rRNA gene sequence identity to Aquimarina hainanensis. Aquimarina sp. TRL1 was demonstrated through comparative genome analysis (99.99 % OrthoANIu) as the bacterium reisolated from experimentally infected phyllosomas presenting with typical signs of WLD. Pereiopod damage was a major predisposing factor to WLD. Histopathological examination of WLD-affected pereiopods showed masses of internalised bacteria and loss of structural integrity, suggesting that Aquimarina sp. TRL1 could enter the circulatory system and cause death by septicaemia. Aquimarina sp. TRL1 appears to have important genomic traits (e.g. tissue-degrading enzymes, gliding motility, aggregate-promoting factors) implicated in the pathogenicity of this bacterium. Bacterial communities of WLD-affected pereiopods showed low bacterial diversity and dominant abundance of Aquimarina spp. compared to healthy pereiopods, which were more diverse and enriched with Sulfitobacter spp. We have shown that Aquimarina sp. TRL1 is the aetiological agent of WLD in cultured Palinurid and Scyllarid phyllosomas and that damaged pereiopods are a predisposing factor to WLD.